Entrepreneurial Orientation, Market Orientation and Performance of Teachers and Researchers in Public Higher Education Institutions. - Felgueira, Teresa (2016)
In this study we intend to analyse the relationships between entrepreneurial orientation, market orientation and performance at the individual level. We propose the concept of individual entrepreneurial orientation (IEO) and a measurement scale, and we use the individual market orientation concept (IMO), measured with i-MARKOR. The main objective is to analyse the relationship between IEO, IMO and performance of teachers and researchers of the public higher education institutions (PHEI). A conceptual model is proposed representing the relationship between these variables. The results of this research can be highly useful in understanding the interaction between the analysed variables and their impact on the PHEI.